EFFECT OF WET MASH WITH OR WITHOUT ADDED PHYTASE ON PHYTATE-P AVAILABILITY: IN VITRO HYDROLYSIS OF PHYTATE - Jubarah, Salah Khatir; Melingasuk, Milton L.; Loma, Rizig E. (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2018)
Dietary wetness is envisaged to augment phytate hydrolysis through enhanced phytate accessibility to phytase, since phytate degradation is water-mediated. In determining the influence of dietary wetness with supplementary phytase on phytate-P availability, four plant-based growers diets were formulated, containing 0.0, 0.1, 0.2 and 0.3g kg-1 added phytase and with the required phosphorus being entirely phytate-P. Dietary moisture contents were reconstituted by addition of three levels of 0.0, 30 and 60 % distilled-deionised water on Dry Matter basis (DM). Dietary treatments were arranged in a factorial randomized complete block design with three replications. The released inorganic phosphorus was determined at 6hr intervals throughout the 24hr incubation period at 24ºC. The 30% and 60% dietary wetness with added phytases significantly increased (P<0.05) inorganic phosphorus output compared to either 0.0% or wetness without added phytase.  At 6hr of incubation, phytase plus 60% wetness had the highest (P<0.05) inorganic phosphorus, while at 12hr 30% dietary wetness plus phytase yielded the highest inorganic phosphorus (P<0.05). Wetness plus phytase had no pronounced effect (P<0.05) beyond 12hr, except at 24hr (P<0.05). Increasing supplementary phytase in association with dietary wetness significantly (P<0.05) increased inorganic phosphorus output, however, setting wet diets beyond 12hr, produced gases and dietary discoloration.